2013
DOI: 10.1002/tox.21848
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes during spermatogenesis, biochemical and hormonal evidences of testicular toxicity caused by TBT in freshwater prawn Macrobrachium rosenbergii (De Man, 1879)

Abstract: The present investigation documents the impact of tributyltin (TBT) on the ultrastructural variation of spermatogenesis in freshwater prawn Macrobrachium rosenbergii. The environmentally realistic concentration of TBT can cause damages to the endocrine and reproductive physiology of crustaceans. In this context, three concentrations viz. 10, 100, and 1000 ng/L were selected and exposed to prawns for 90 days. The TBT exposed prawn exhibited decrease the reproductive activity as evidenced by sperm count and sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…Revathi et al 2014 reported that the TBT with three concentration levels such as 10, 100, and 1000 ng L −1 clearly manifests the deleterious effects on spermatogenesis, reduction in testosterone level, and impairment in the reproductive system of freshwater male prawn, M. rosenbergii. In an another study, from the same dose levels of TBT administration has remarkable impact on the testicular development, impairment of spermatogenesis as well as decrease of testosterone level in the freshwater male prawn, M. rosenbergii (Revathi et al 2012). The present results agree with the aforementioned observations, and this study clearly indicates the impact of TBT on the antioxidant and DNA damage response in spermatozoa of freshwater prawn M. rosenbergii.…”
Section: Resultssupporting
confidence: 95%
“…Revathi et al 2014 reported that the TBT with three concentration levels such as 10, 100, and 1000 ng L −1 clearly manifests the deleterious effects on spermatogenesis, reduction in testosterone level, and impairment in the reproductive system of freshwater male prawn, M. rosenbergii. In an another study, from the same dose levels of TBT administration has remarkable impact on the testicular development, impairment of spermatogenesis as well as decrease of testosterone level in the freshwater male prawn, M. rosenbergii (Revathi et al 2012). The present results agree with the aforementioned observations, and this study clearly indicates the impact of TBT on the antioxidant and DNA damage response in spermatozoa of freshwater prawn M. rosenbergii.…”
Section: Resultssupporting
confidence: 95%
“…The number of sperm cells observed for several decapod species is a proxy for sperm quality (Bugnot & López‐Greco, ; Claudet et al, ; Coman et al, ; Harlıoğlu, Kutluyer, & Gür, ). M. rosenbergii, with an average weight of 16 g produces 2.5 × 10 6 sperm cells per spermatophore (Revathi, Iyapparaj, Vasanthi, Munuswamy, & Krishnan, ); 5.2–5.8 × 10 8 sperm cells for males of 24 ± 10 g weight (Harris & Sandifer, ); and 6 ± 4 × 10 9 for males with an average body weight of 45 ± 4 g (Claudet et al, ). Although M. rosenbergii has remarkable variability in sperm numbers per spermatophore (up to three orders of magnitude), this species shows a direct correlation between body size of the male and the number of sperm cells contained in the spermatophores.…”
Section: Discussionmentioning
confidence: 99%
“…Since this effect did not occur in the eyestalk-ablated crabs, it is possible that OTs injection caused CHH secretion ( 72 ). In M. rosenbergii , the treatment with TBT (10, 100, and 1000 ng L −1 ) dissolved in water for 90 days also increased glucose levels in the hemolymph ( 73 ). Therefore, synthesis, release, and secretion of CHH and its signaling are processes that could be disrupted as the result of OTs exposure and needs to be further investigated.…”
Section: Ots Effects On the Metabolismmentioning
confidence: 99%
“…These metabolites are distinctively mobilized during diverse types of stresses, reflecting homeostasis alterations that can be used as biomarkers of health and stress condition ( 31 , 37 , 46 , 47 , 79 ). In the freshwater prawn M. rosenbergii , TBT (10, 100, and 1,000 ng L −1 ) treatment reduced hepatosomatic index (HIS) and the content of proteins, glycogen, and lipids in the hepatopancreas in a dose-dependent manner ( 73 ). In the cladoceran Daphnia magna , lipids are stored in spherical lipid droplets scattered throughout the body, and treatment with 0.036 or 0.36 µg L −1 increased lipid fluorescent stain ( 80 ).…”
Section: Ots Effects On the Metabolismmentioning
confidence: 99%
See 1 more Smart Citation